2020
DOI: 10.1016/j.ebiom.2020.102698
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells combined with ultra-purified alginate gel as a regenerative therapeutic strategy after discectomy for degenerated intervertebral discs

Abstract: Background: Because the regenerative ability of intervertebral discs (IVDs) is restricted, defects caused by discectomy may induce insufficient tissue repair leading to further IVD degeneration. An acellular bioresorbable biomaterial based on ultra-purified alginate (UPAL) gel was developed to fill the IVD cavity and prevent IVD degeneration. However, an acellular matrix-based strategy may have limitations, particularly in the elderly population, who exhibit low self-repair capability. Therefore, further trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(89 citation statements)
references
References 30 publications
5
84
0
Order By: Relevance
“…3,4,8,11À14,16 To identify the course of post-surgical IVD degeneration from the onset, we generated a rabbit model of IVD degeneration. 2,15 We demonstrated that following discectomy, the use of UPAL gel alone suppressed IVD degeneration compared to the extent of degeneration without UPAL gel treatment. Additionally, the combination of allogenic BMSCs and UPAL gel was more effective at inducing IVD regeneration compared to UPAL alone.…”
Section: Implications Of All the Available Evidencementioning
confidence: 92%
See 1 more Smart Citation
“…3,4,8,11À14,16 To identify the course of post-surgical IVD degeneration from the onset, we generated a rabbit model of IVD degeneration. 2,15 We demonstrated that following discectomy, the use of UPAL gel alone suppressed IVD degeneration compared to the extent of degeneration without UPAL gel treatment. Additionally, the combination of allogenic BMSCs and UPAL gel was more effective at inducing IVD regeneration compared to UPAL alone.…”
Section: Implications Of All the Available Evidencementioning
confidence: 92%
“…18 A carrier biomaterial is necessary to prevent cell leakage during discectomy. 2,15 To date, no biomaterials have been clinically approved for this purpose because each biomaterial did not meet criteria for both biologic and mechanical safety. We had previously developed an original, acellular, bioresorbable, ultra-purified alginate (UPAL) gel to repair IVD degeneration in small 2,3,15,16 and large animal models in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In an article in EBioMedicine, Ukeda and co-workers report the development of a novel regenerative therapeutic strategy that involves the application of bone marrow-derived mesenchymal stem cells (BMSCs) combined with a hydrogel [6]. The bioresorbable hydrogel consisted of ultra-purified alginate (UPAL), a polysaccharide derived from the brown seaweed, Phaeophyceae, which gelates via calcium ion-mediated crosslinking.…”
mentioning
confidence: 99%
“…However, it is not known that BMSCs have a reciprocal stimulatory effect on NPCs. The Contents lists available at ScienceDirect EBioMedicine journal homepage: www.elsevier.com/locate/ebiom encapsulation of BMSCs by Ukeda et al [6] likely enhanced the retention of BMSC-secreted factors, resulting in enhancement of NPC bioactivity observed in the 3D in vitro cultures, as well as activation of resident NPCs in the site of IVD degeneration in vivo. The absence of osteophyte formation also indicated that the rapid curing of the UPAL hydrogel prevented leakage of BMSCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation